The Beaver River country : an Adirondack history - Pitts, Edward I. (Syracuse University Press, 2022)
"This book is the first comprehensive history of the remote section of the western Adirondacks surrounding the upper reaches of the Beaver River. It contains the previously untold stories of early settlement, the advent of sporting tourism, the creation of the Stillwater Reservoir, the effects of the coming of the railroad, the vanished Beaver River Club, the Rap-Shaw Club and much more, all illustrated with rare vintage photographs"--